2004
DOI: 10.1086/421054
|View full text |Cite
|
Sign up to set email alerts
|

DNA/RNA Helicase Gene Mutations in a Form of Juvenile Amyotrophic Lateral Sclerosis (ALS4)

Abstract: Juvenile amyotrophic lateral sclerosis (ALS4) is a rare autosomal dominant form of juvenile amyotrophic lateral sclerosis (ALS) characterized by distal muscle weakness and atrophy, normal sensation, and pyramidal signs. Individuals affected with ALS4 usually have an onset of symptoms at age <25 years, a slow rate of progression, and a normal life span. The ALS4 locus maps to a 1.7-Mb interval on chromosome 9q34 flanked by D9S64 and D9S1198. To identify the molecular basis of ALS4, we tested 19 genes within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
477
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 711 publications
(502 citation statements)
references
References 26 publications
11
477
1
5
Order By: Relevance
“…It was recently shown that SMN recruits senataxin, an RNA:DNA helicase involved in R-loop resolution, to transcription termination sites (28). Intriguingly, senataxin itself is mutated in a juvenile-onset form of ALS, designated ALS4, that bears a striking resemblance to SMA and results in loss of motor neurons in early childhood (59). An additional RNA:DNA helicase, IGHMBP2, was initially characterized in the context of R-loop-dependent class-switch recombination, but it has since been found that loss-of-function mutations in IGHMBP2 cause spinal muscular atrophy type I with respiratory distress (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that SMN recruits senataxin, an RNA:DNA helicase involved in R-loop resolution, to transcription termination sites (28). Intriguingly, senataxin itself is mutated in a juvenile-onset form of ALS, designated ALS4, that bears a striking resemblance to SMA and results in loss of motor neurons in early childhood (59). An additional RNA:DNA helicase, IGHMBP2, was initially characterized in the context of R-loop-dependent class-switch recombination, but it has since been found that loss-of-function mutations in IGHMBP2 cause spinal muscular atrophy type I with respiratory distress (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] In some forms of ALS, such as the SETX-associated ALS type 4, the phenotype is so atypical that some authors suggest they should be considered as separate disease entities rather than ALS. 20,21 60% of patients with disease onset between 20 and 40 years of age have predominantly upper motor neuron involvement, and relatively few of these patients (15%) have bulbar-onset disease. 15 Older age at onset is associated with decreased likelihood of upper motor neuron involvement (20%), increased probability of bulbar onset (some studies report up to 50% with onset after 80 years of age), and poor prognosis.…”
Section: Age At Onsetmentioning
confidence: 99%
“…2 Mutations in other genes cause rarer forms of ALS. These genes include Sentaxin, a DNA/RNA helicase that causes juvenile ALS, 3 Alsin, 4,5 Dynactin, 6,7 angiogenin, 8 and synaptobrevin associated membrane protein B. 9 Sporadic ALS, which accounts for more than 90% of ALS cases, has been more difficult to genetically solve.…”
Section: Introductionmentioning
confidence: 99%